A Case of BeckwithWiedemann Syndrome with Polyhydramnios - Yusrawati, Yusrawati; Muhatiah, Reno (Indonesian Journal of Obstetrics and Gynecology, 2017)
Objective: To report a rare case of Beckwith-Wiedemann Syndrome with polyhydramnios. Methods: Reporting a case of Beckwith-Wiedemann syndrome with polyhydramnios. Results: Case of Mrs. Y, 27 years old woman, G2P1A0L1 preterm pregnancy (30-31 weeks) with polyhidramnios. From ultrasound found renomegaly, bilateral hyperechogenic polycystic kidney, and the karyotype result was 46,XX. Caesarean section was performed due to fetal distress. A female baby was born by caesarean section with birth weight of 1300 grams, 37 centimeters of body length, and APGAR score of 6/8. The congenital anomalies found were hepatomegaly, renomegaly, bilateral hyperechogenic renal polycystic, low set ears. The baby was died in NICU on day care 5th, with suspected of sepsis. Conclusion: Prenatal diagnosis of Beckwith-Wiedemann syndrome on fetus with polyhydramnios. [Indones J Obstet Gynecol 2017; 5-3: 185-188] Keywords: amniocentesis, beckwith-wiedemann syndrome, polyhydramnios, prenatal diagnostic, USG